2002
DOI: 10.1177/009127002401382632
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Trial between Artemether-Lumefantrine (Riamet®) and Quinine in Healthy Subjects

Abstract: Forty-two healthy Caucasian subjects were randomized in a double-blind, parallel three-group study (14 subjects per group) to investigate potential electrocardiographic and pharmacokinetic interactions between the antimalarials artemether-lumefantrine (six-dose regimen of Riamet over 3 days) and quinine (2-h intravenous infusion of 10 mg/kg body weight, not exceeding 600 mg in total, 2 h after the last dose of Riamet). The study medications were all safe and well tolerated after all treatments. Neither the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
19
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 45 publications
6
19
1
1
Order By: Relevance
“…The AUCs for ARM and DHA in the present study were similar to those reported previously in adults with malaria (21, 24) but higher than those in healthy adults (14,19,20). Our terminal elimination half-life for ARM was longer than those reported in these studies (16.4 versus 1.5 to 3.9 h), while for DHA, it was shorter (0.80 versus 1.2 to 2.1 h).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The AUCs for ARM and DHA in the present study were similar to those reported previously in adults with malaria (21, 24) but higher than those in healthy adults (14,19,20). Our terminal elimination half-life for ARM was longer than those reported in these studies (16.4 versus 1.5 to 3.9 h), while for DHA, it was shorter (0.80 versus 1.2 to 2.1 h).…”
Section: Discussionsupporting
confidence: 88%
“…Both ARM and DHA have short half-lives (14, 19-21, 24, 25, 31) but a rapid effect on parasitemia. LUM is a highly lipophilic drug with a longer half-life (11,13,14,19,20,24,30) which is combined with ARM primarily to prevent late recrudescence. Although the pharmacokinetic (PK) properties of ARM, DHA, and LUM in adults have been well documented (4, 5, 11, 13-15, 19-22, 24, 30), there are scant and inconsistent data relating to the disposition of desbutyl-lumefantrine (DBL), a potent LUM metabolite (26,28,29,32) that may influence AL's treatment outcome (32).…”
mentioning
confidence: 99%
“…The predicted median LUM concentration on day 3, calculated from 1,000 realizations of the pharmacokinetic model under the study conditions, came to 9.3 M and was similar to the median of 11.3 M reported by Checci and colleagues from pediatric patients in Uganda (4). The typical value of CL/F was estimated to 77 ml/h/kg, which is within the range of 40 to 200 ml/h/kg reported in adults (6,16).…”
Section: Discussionsupporting
confidence: 82%
“…Follow-up duration was 72 h. A clinical assessment was performed at 0, 2,4,8,16,24,36,48,60, and 72 h. This included a physical examination and questions related to malaria-associated symptoms/ potential side effects of the study drug as well symptoms and/or signs of severe malaria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation